TREN BAHASA DAN IDENTITAS KOLEKTIF SANTRI DALAM PENGGUNAAN BAHASA GAUL: STUDI BAHASA “MENYALA ABANGKUH” - Sari Ani; Inayatur Rahman; Fetty Khoiriyah (Pendidikan Bahasa dan Sastra Indonesia, 2024)
This study aims to describe and explain language trends in influencing social interactions and group dynamics among students and the positive or negative impacts of the use of the language trend